CHARACTER EDUCATION OF CHILDREN'S PERSPECTIVE IBN QAYYIM AL-JAWZIYYAH (691 H - 752 H) - Makmudi Makmudi Makmudi (State Islamic University of North Sumatra Indonesia, 2017)
Abstract, The main problematic that caused the crisis of character in children is not making belief as basic philosophical in education. So, the implication of this is freedom of excessive euphoria. The success of the child based only from the perspective of the child's success in academic course. While the values of ethics, morals, and character less getting serious attention. Therefore, even though the students excel in intelligence quotient (IQ), but in emotional quotient (EQ) they are in crisis of becoming alarming character. In this context, the existence of children's character education is considered very important for the next generation as an integral part of their life and living. The purpose of this study was to determine the thinking of Ibnu Qayyim al-Jawziyya about the concept of character education of children. The method of writing this research use library research (library research), the research done by collecting data and information by reading, studying and then analyze literatures relating to the theme, both primary (primary sources) and secondary (secondary sources ). Then analyzed using content analysis method (content analysis) in the form of descriptive-Analytic. The results of the research in this dissertation shows that the concept of character education of children according to Ibnu Qayyim al-Jawziyya emphasis on the four major ways : 1. The importance of introducing kids about the monotheistic God, 2. The need to teach children the principal teachings of religion, 3. Teach and familiarize children on good ethics and morals, 4. Modeling, 5. Praise and meaningful punishment.